Representasi Bullying di Sekolah Dasar: Studi Kasus di Sekolah Model dan Pembina - Ferry Aristya (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2020)
The purpose of this study is to represent bullying in one of the Model elementary schools in Sragen. This research adopts a qualitative approach, which is a case study, to reach the goal. The research subjects are all teachers and students of Model Elementary Schools. Data collected by observation and in-depth interviews. The results of this study describe (1) the impact shown by victims of both female and male gender and audience reactions; (2) forms of bullying; 3) handling bullying. Detailed results and discussion can be seen in this article. Keywords: representation, bullying, preventive, elementary school